2001
DOI: 10.1007/s001250100580
|View full text |Cite
|
Sign up to set email alerts
|

The role of impaired early insulin secretion in the pathogenesis of Type II diabetes mellitus

Abstract: Normal glucose tolerance is maintained by a precise balance between insulin secretion from pancreatic beta cells and insulin action on sensitive tissues, principally muscle, adipose tissue and liver [1,2]. Patients with Type II (non-insulin-dependent) diabetes mellitus manifest impairments in insulin secretion and insulin action and an increased rate of endogenous glucose production [1±3]. The relative importance of these abnormalities in the pathogenesis of the disease has been debated for many years. It is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
274
0
8

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(300 citation statements)
references
References 37 publications
18
274
0
8
Order By: Relevance
“…In comparative studies of several indices of beta cell function, the IGI index was closely correlated with insulin secretion [29]. Recent studies have presented results that indicate that beta cell dysfunction in early stages of AGT is present independently of insulin resistance and is already present in obese patients with NGT [30][31][32]. In addition, a study of type 2 diabetic Japanese patients recently showed that decreased insulin secretion had a more pronounced impact on glucose tolerance than insulin sensitivity [33].…”
Section: Discussionmentioning
confidence: 99%
“…In comparative studies of several indices of beta cell function, the IGI index was closely correlated with insulin secretion [29]. Recent studies have presented results that indicate that beta cell dysfunction in early stages of AGT is present independently of insulin resistance and is already present in obese patients with NGT [30][31][32]. In addition, a study of type 2 diabetic Japanese patients recently showed that decreased insulin secretion had a more pronounced impact on glucose tolerance than insulin sensitivity [33].…”
Section: Discussionmentioning
confidence: 99%
“…The respective roles of insulin deficiency and insulin resistance in the development of Type 2 diabetes mellitus remain controversial [1,2]. In response to a glucose stimulus, two phases of insulin secretion may be distinguished [3].…”
Section: Introductionmentioning
confidence: 99%
“…Both impaired insulin sensitivity and insulin secretion are involved in the deterioration of glucose tolerance from the normal to the glucose intolerant state [12]. Whether defects in these glucose-insulin metabolism parameters are present in subjects with high normal 2hPG (NPG) is not well known.…”
Section: Introductionmentioning
confidence: 99%